Effect of fracture energy estimation on the predictions of mode II behavior of bonded joints using cohesive zone models - Michele Perrella; Enrico Armentani; Giuseppe Lamanna; Valentino Paolo Berardi (Fracture and Structural Integrity)
Fracture behavior of adhesive joints is an important topic in structural design of new structural elements or in retrofitting of existing ones. The mechanical models available in literature capable of predicting the failure mode of these junctions are mainly formulated within the cohesive zone model (CZM). Direct approaches for identification of CZM parameters in pure mode II of bonded joints, based on different modelling of strain energy release rate (SERR), are presented. The mode II SERR was determined from experimental results on end notched flexure (ENF) tests. Digital image correlation (DIC) analysis was used to evaluate the shear slip displacements of adhesive layer. The mode II cohesive traction-separation law was identified by numerical differentiation of SERR and best fit equation systems were adopted for an analytical description of cohesive interface behavior. Moreover, the obtained CZM laws were used for predicting the decohesion process by finite element analyses. Global and local responses of ENF test were compared with experimental data in terms of load-displacement and adhesive tangential displacement-time curves, respectively. A more accurate modelling of fracture energy resulted in a sounder agreement of prediction with experimental data.